PROSES PERCEPATAN DIFUSI INOVASI PRODUK SUSU STERILISASI NONTHERMAL - Andi Ridwan Makkulawu (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Diffusion of innovation theory essentially describes the process of how an innovation isdelivered (communicated) through certain channels over time to a group of members of thesocial system. In this paper will be presented a study of the diffusion of innovations that resultedfrom the innovative work that milk sterilizer with electric shock (electric milk) to help dairyfarmers in maintaining the quality of milk yield. Analytical methods to accelerate the innovationdiffusion theory of Rogers conducted the assessment associated with knowledge management tomeasure innovation performance. From the results of the study, electric sterilizer milk is aninnovation because they have been commercialized to the public, especially in the MilkProcessing Cooperative (PPP) milk and dairy farmer groups. In functional electrical appliancemilk can be accepted by the public because the operating system can be run automaticallymaking it easier for users of the technology in terms of the operation of the appliance. Toaccelerate the diffusion of innovation will require accelerating the dissemination of tools withtool usage in group level, as did the level rancher PPP.